VERIFIKASI DOSIMETRI PERHITUNGAN BERKAS TERBUKA PERANGKAT LUNAK IN-HOUSE TREATMENT PLANNING SYSTEM (TPS) PESAWAT TELETERAPI COBALT-60 - Intan A. S. Mu'minah; La Ode Husein Z. T.; Supriyanto A. Pawiro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Currently, cobalt-60 teletherapy units still often used for radiotherapy treatments in Indonesia. An in-house treatment planning systems (TPS) was developed by Medical Physics and Biophysics Laboratory (LFMB) Universitas Indonesia as a treatment planning software of cobalt-60 beams. Performance validation of TPS calculation is an important parameter in radiotherapy quality assurance (QA). Measurements of absorbed dose using fixed SSD treatment technique were done for 44 planning test case datasets for open beam condition with different field sizes and depths of target (isocenter). A mean dose deviations (1.810 Â± 2.469) % indicate that in-house TPS calculations for open beam conditions appropriate for clinical tolerances of TPS calculation.Keywords: cobalt-60 beams, dose deviation, in-house TPS, open beams, quality assurance.